Reference service delivery system in west-Africa: limitations and prospects as seen from Kenneth Dike Library, Nigeria (2010)
This paper focuses on the centrality of reference services to the practice of librarians hip. It enumerates the limitations faced by Kenneth Dike Library (KDL) in its bid to deploy Information Communications Technology (lCT) to its reference services delivery system. Being a university library in a developing country, KDL has to cope with the problems confronting universities in Nigeria. The problems that plague the ivory towers and, consequently, the libraries that serve them, include lack of proper funding, infrastructural deficiencies, inability to retain information technology experts, and intra-local politics regarding the control of ICT facilities in the library. The paper also projects on KDL's efforts at establishing the virtual reference suite to complement its present reference services